Ma'mun: THE EFFECT OF MODIFICATION OF THE CHAN PASSING GAME ON THE BOTTOM PASSING SKILL OF VOLLEYBALL - Sukron Ma'mun; Nurhalim Nurhalim (Cakrawala Pedagogik, 2021)
This Research aim tyo know the effect of chain passing game modification exercise on volleyball bottom passing skills. The study used a quasi-experimental method. Sampling using random sampling. The independent variable of this research, namely, modofication of chain passing, as the dependent variable, namely passing under the population of this study at SMK Al-Ihya Kaduronyok and the sample of this study amounted to 16 people. The results of the study showed that there as an effect of modification of the chain passing gam eon volleyball under passing skills in extracuricular activities at Al-Ihya Kaduronyok Vocation School. This is evidenced by the significance value at Tcount=6.0797>Ttable=1.687. The average value of the pretest result was 7.375 while the posttest increased to 18.5. Based on hypothesis testing, i tis stated that there is a positive influence berween the effect of modofying the chain passing gme on vollyball bottom passing skills. A good passing player isable to return the ball wwell ti this friend or can hold the ball by not deviating and just at the times of his passing.